Analisa dan perancangan berorientasi objek pada sistem informasi geografis untuk menentukan lokasi irigasi sungai - Dimas Dwi Randa (JRTI (Jurnal Riset Tindakan Indonesia), 2022)
The government in Indonesia is starting to change the perspective so that all levels of government use a computerized system called e-government. Especially in the government environment in West Sumatra Province. Currently, West Sumatra Province is still far behind other provinces that have utilized information technology. Therefore, the Province of West Sumatra tries to utilize technology for existing agencies throughout the province of West Sumatra. One of them is at the Water Resources Management Office of West Sumatra Province. The application technology needed by PSDA is a geographic information system wherein building the application requires a work system framework design method, OOAD, the modeling uses UML and uses the PHP programming language as well as storage media for all irrigation data and coordinates using a MySQL database so that all applications will be implemented. built to make it easier for the PSDA to enter website-based coordinate data.